PRZESŁANKI OGRANICZENIA WŁADZY RODZICIELSKIEJ NA ZIEMIACH POLSKICH - Długoszewska, Iwona (Zeszyty Prawnicze, 2016)
Reasons for Restricting Parental in the Polish Lands Summary This article presents the limits of parental authority and, in particular, the condition of this limitation in historical perspective. The analysis of this institution begins the tenth century, and ends on the current Code and caring family. The primary objective of the article is to present the evolution of the institution of parental restrictions. Various stages of this evolution in Poland have been preceded by a brief general remarks on the regulation of this institution in Europe. The analysis serves primarily to a better understanding of the institution itself limits of parental authority, but also allows the presentation of the history of the Polish legal system over the centuries.